2017
DOI: 10.1159/000458771
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Stress and Severe Obesity: A Case-Control Study

Abstract: Background: Several etiological factors for obesity have been identified, whereas other factors related to obesity, such as stress, remain poorly understood. This study used psychiatric methods to examine the relationship between stress and obesity. Methods: Matched study and control groups were established, and the female and male control subjects were selected separately by random sampling. The control subjects were matched with the case subjects with respect to place of residence, sex, age, date that a pens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Consistent with the above finding, other studies also reported a significant relationship between stress and obesity in a way that stress and depression are dangerous starting points for nutrition disorders ( Farahmand et al, 2019 ; Hokm Abadi et al, 2014 ; Koski & Naukkarinen, 2017 ). In other words, stressful conditions lead to disordered diet, lack of physical activity, and sleep and excitement disorders, each of which can independently lead to obesity in male nurses.…”
Section: Discussionsupporting
confidence: 62%
“…Consistent with the above finding, other studies also reported a significant relationship between stress and obesity in a way that stress and depression are dangerous starting points for nutrition disorders ( Farahmand et al, 2019 ; Hokm Abadi et al, 2014 ; Koski & Naukkarinen, 2017 ). In other words, stressful conditions lead to disordered diet, lack of physical activity, and sleep and excitement disorders, each of which can independently lead to obesity in male nurses.…”
Section: Discussionsupporting
confidence: 62%
“…These letters are available upon request [1]. Table 1 shows the basic characteristics of the study participants [2].…”
Section: Methodsmentioning
confidence: 99%
“…GLIM analysis is straightforward when the data are in a convenient individual-by-individual format, which commonly corresponds to the method compilation. A major advantage of this technique is that it is easy to use and has inherent flexibility [1] [2]. In each set, one case was included for every 0 -5 controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Living in a demanding environment, trying to seize the time as efficiently as possible may lead not only in bad food choices, less time to work out but maybe can change normal functions of the body through production of hormones such as cortisone that contributes to gain weight. 5,6 c. Inadequate sleep: The sleep duration is associated with the BMI. People who sleep less than 7-9 hours per night have higher BMI and have abdominal obesity according to a study that used data from the National Health and Nutrition Examination Survey (NHANES) 2005-2010.…”
Section: B Stressmentioning
confidence: 99%